Expansion of the genetic and phenotypic spectrum of hereditary spastic paraplegia caused by ABHD16A gene variants: an integrated analysis based on novel variants and literature review - He, Manling; Zhang, Qiang; Chen, Shaoke; Li, Chuan; Xie, Bobo; Zhao, Qingxiu; Huang, Yiyun; Fan, Xin (Frontiers in Pediatrics, 2026)
BackgroundHereditary spastic paraplegia (HSP) is a clinically and genetically heterogeneous neurodegenerative disorder. Biallelic pathogenic variants in ABHD16A have recently been linked to a neurodevelopmental phenotype featuring early-onset spasticity and global developmental delay.ObjectiveTo further define the clinical and genetic spectrum of ABHD16A-associated disease through the characterization of a novel pediatric case and an updated literature review.MethodsWe evaluated a child presenting with global developmental delay and progressive spastic paraplegia. Whole-exome sequencing (WES) was performed, and candidate variants were validated by Sanger sequencing. Clinical features were documented prospectively, and a systematic review of published cases was conducted to assess phenotypic patterns and genotype–phenotype relationships.ResultsConsistent with prior reports, the core features of ABHD16A-related disease include global developmental delay, intellectual disability, and spastic paraplegia, often with early onset. In our patient, tandem mass spectrometry revealed elevated long-chain acylcarnitines (C16, C18:1, C18:2)—a metabolic abnormality not previously described in this condition. WES identified two novel compound heterozygous frameshift variants in ABHD16A: c.119delA (p.His40Leufs49) and c.559_562del (p.Pro187Cysfs29), both confirmed by Sanger sequencing and classified as pathogenic (ACMG criteria: PVS1, PM2, PM3, PP1). Our literature review identified 17 additional individuals from 9 families, enabling a refined clinical delineation: most patients exhibited motor and speech delay, axial hypotonia evolving into spasticity, and variable degrees of cognitive impairment.ConclusionsTo our knowledge, this is the first reported case of ABHD16A-related neurodevelopmental disorder in a Chinese patient. We provide a detailed phenotypic characterization and an updated review of the published literature to support clinical recognition and genetic diagnosis of this emerging condition.